Multi-region lifetime assessment of reinforced concrete structures subjected to carbonation and climate change. (November 2022) - Bastidas-Arteaga, E.; Rianna, G.; Gervasio, H.; Nogal, M.
Abstract: The built environment is already facing severe consequences related to climate change. Considering the durability of structures, the increase of carbon-dioxide (CO2 ) concentration and changes on temperature and relative humidity may accelerate carbonation-induced corrosion, thus affecting the service life of reinforced concrete structures. Several studies have assessed the potential effects of climate change on concrete carbonation for specific locations, and this requires to convert climate databases, which come in various spatial resolutions, to scales that are suitable for the purpose of the study. However, there is not a consistent methodology for using climate projections databases at various spatial scales (e.g., city, district, region, country, etc.). Hence, the main goal of this research is to propose an approach allowing for multi-region assessment of carbonation of reinforced concrete structures, under changing climate. The proposed methodology is based on a carbonation model that takes into account the effects of climate change over time. Moreover, procedures and recommendations are provided to reduce errors in lifetime assessment, such as selection of climate change scenarios, choice of simulation chains, and bias correction. The use of the proposed approach is illustrated by computing carbonation depths for several places located in three districts in Portugal: Porto (north), Lisboa (Middle), and Faro (South). The overall results allow to conclude that: (i) specific climate conditions inside a district, namely temperature and relative humidity, modify the carbonation depths (e.g.: a variation of 19 % was obtained for the carbonation depth in the district of Lisbon); (ii) bias-correction should be systematically carried out to avoid errors in the assessments (for example, in the district of Faro, the time to initiate corrosion was over estimated by about 7 years without bias correction); and (iii) climate change could accelerate concrete carbonation of structures in the different locations considered in Portugal (under the most pessimistic climate scenario, the time to corrosion initiation was below 100 years for all locations).